Every story has two sides: evaluating information processing and ecological dynamics perspectives of focus of attention in skill acquisition - Gottwald, Victoria; Davies, Marianne; Owen, Robin (Frontiers in Sports and Active Living, 2023)
Directing our focus of attention appropriately during task execution can benefit outcome performance, cognitive efficiency, and physiological efficiency. For instance, individuals may benefit from adopting an external focus of attention (i.e., by focusing attention on the effects of one’s movements on the environment) over an internal focus of attention (e.g., focusing on one’s body movements). However, accounts concerning the theoretical functioning of such effects have primarily relied on hierarchical information processing perspectives; far less consideration has been given to potentially alternative explanations based on ecological dynamics, instances where an internal focus may be desirable over an external focus, and the associated applied implications. Within the present review, we: (a) outline the most recent developments in attentional focus research; (b) evaluate similarities and differences between information processing and ecological dynamics explanations of the focus of attention effect; (c) provide practical recommendations; and (d) discuss future research avenues. In doing so, a case is made for an ‘Ecological Dynamics Account of Attentional Focus’ to act as an alternative to information processing-based hypotheses.